2009
DOI: 10.1103/physrevlett.103.225501
|View full text |Cite
|
Sign up to set email alerts
|

Shock Compression of Quartz to 1.6 TPa: Redefining a Pressure Standard

Abstract: Evaluation of models and theory of high-pressure material response is largely made through comparison with shock wave data, which rely on impedance match standards. The recent use of quartz as a shock wave standard has prompted a need for improved data. We report here on measurements of the quartz Hugoniot curve from 0.1-1.6 TPa. The new data, in agreement with our ab initio calculations, reveal substantial errors in the standard and have immediate ramifications for the equations of state of deuterium, helium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
167
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 23 publications
8
167
1
Order By: Relevance
“…However, shock compression cannot access all values of temperature and pressure. Hugoniot states for D 2 up to ∼100 GPa achieved by gas-guns (Nellis et al, 1983a), pulsed laser (Da Silva et al, 1997), magnetically-driven flyers (Knudson and Desjarlais, 2009), and hemispherically converging explosives (Boriskov et al, 2005) are shown in Fig. 1.…”
Section: A Dynamical Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, shock compression cannot access all values of temperature and pressure. Hugoniot states for D 2 up to ∼100 GPa achieved by gas-guns (Nellis et al, 1983a), pulsed laser (Da Silva et al, 1997), magnetically-driven flyers (Knudson and Desjarlais, 2009), and hemispherically converging explosives (Boriskov et al, 2005) are shown in Fig. 1.…”
Section: A Dynamical Compressionmentioning
confidence: 99%
“…A number of techniques have been developed to produce shocks, including gas guns (Nellis et al, 1983a), laser-driven compression (Collins et al, 1998a,b;Da Silva et al, 1997;Hicks et al, 2009;Sano et al, 2011b), magnetically driven flyers (Knudson and Desjarlais, 2009;Knudson et al, 2001Knudson et al, , 2004, and hemi-spherically converging explosives (Boriskov et al, 2005). Because the shock process is adiabatic, large increases in temperature also occur with the increases in pressure.…”
Section: A Dynamical Compressionmentioning
confidence: 99%
“…These data, in conjunction with QMD calculations for quartz, have provided a new understanding of quartz in the multi-Mbar regime. In particular, it appears that the dissociation of quartz extends over a range spanning nearly 100-1000 GPa, much larger than previously expected [12]. This is significant given the prolific use of quartz as a standard in recent multi-Mbar experiments.…”
Section: Shock Compression Platformmentioning
confidence: 63%
“…This is significant given the prolific use of quartz as a standard in recent multi-Mbar experiments. In particular, the revision of this standard has resulted in corrections in the inferred density of deuterium of ~10-15% [12]. Even larger corrections may be necessary for higher compressibility materials such as helium [13].…”
Section: Shock Compression Platformmentioning
confidence: 99%
“…The AM05 functional has been used for calculating various material properties of miscellaneous systems [28][29][30][31] and is proven to perform exceptionally well for solids and surfaces. However, the performance is not as good for systems of more localized characters due to the lack of description of confinement physics in the functional as we discussed in Sec.…”
Section: Exchange-correlation Functionals and The Subsystem Functmentioning
confidence: 99%